2019
DOI: 10.1016/j.jtcvs.2018.08.104
|View full text |Cite|
|
Sign up to set email alerts
|

Intermediate-term outcomes of aortic valve replacement with bioprosthetic or mechanical valves in patients on hemodialysis

Abstract: Objective: To investigate the influence of choice of prosthesis (bioprosthetic valves or mechanical valves) on intermediate-term outcomes in patients on hemodialysis undergoing aortic valve replacement (AVR).Methods: A multi-institutional retrospective cohort study was conducted in 18 Japanese centers. All adult patients on chronic hemodialysis who underwent AVR from 2008 and 2015 were included (n ¼ 491). The early and late results were compared between groups. The hazard ratios were calculated using Cox regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…9,10 However, considerable heterogeneity has remained unexplored, and the effects of the valve position and postoperative anticoagulation protocol have still not been clarified. Furthermore, recent publications differ in their outcomes, with Chan and colleagues 11 favoring MPs over BPs regarding long-term survival rates, and Nakatsu and colleagues, 12 Hori and colleagues, 13 Manghelli and colleagues, 14 and Ikeno and colleagues 15 concluding that the survival difference is negligible. Therefore, we integrated every relevant study to update the comparative effectiveness and safety of MPs and BPs in dialysis-dependent patients.…”
Section: See Commentary On Page XXXmentioning
confidence: 99%
“…9,10 However, considerable heterogeneity has remained unexplored, and the effects of the valve position and postoperative anticoagulation protocol have still not been clarified. Furthermore, recent publications differ in their outcomes, with Chan and colleagues 11 favoring MPs over BPs regarding long-term survival rates, and Nakatsu and colleagues, 12 Hori and colleagues, 13 Manghelli and colleagues, 14 and Ikeno and colleagues 15 concluding that the survival difference is negligible. Therefore, we integrated every relevant study to update the comparative effectiveness and safety of MPs and BPs in dialysis-dependent patients.…”
Section: See Commentary On Page XXXmentioning
confidence: 99%
“…Reduced thrombotic complications also contradict the findings of Nakatsu and colleagues, 5 who recently examined 491 dialysis-dependent patients requiring mechanical versus bioprosthetic AVR across 18 Japanese centers and found no difference in thromboembolic events at 5-year follow-up. In contrast to Ikeno and colleagues 4 and colleagues, Nakatsu and colleagues 5 focused on patients requiring AVR, and their larger sample size may have allowed them better to capture a representative sample of this specific subpopulation, without necessarily offering generalizability to patients requiring mitral valve replacement or double valve replacement.…”
mentioning
confidence: 59%
“…Patients on dialysis have a limited lifespan, but mechanical valves are superior to biological valves for midterm results [Greason 2014]. Rehospitalization due to bleeding was a little more frequent with mechanical valves, but Chan et al [2019] reported that the use of mechanical valves in patients on dialysis is appropriate Chan et al [2019] compared 323 patients with a biological valve and 168 patients with a mechanical valve and reported no significant differences in in-hospital mortality, 5-year postoperative survival, or 5-year reoperation-free rate Nakatsu et al [2019]. We believe that multiple factors should be considered when choosing a valve for patients with aortic valve stenosis on hemodialysis.…”
Section: Discussionmentioning
confidence: 99%